Effect of structural parameters on thermal protective performance and comfort characteristic of fabrics. Issue 8 (3rd August 2017) - , Udayraj; Talukdar, Prabal; Das, Apurba; Alagirusamy, Ramasamy
Abstract: In an attempt to understand the influence of basic structural parameters of fabrics on thermal protection and comfort, present study mainly focuses on analyzing effect of fabric weaving pattern and fabric weight. Fabric samples of three basic weaving patterns (plain, twill, and satin) and three different weights were prepared. Air permeability of the developed fabric samples was measured. Thermal protective performance of fabrics against radiant heat and flame exposures of two different intensities were measured. Spectral transmission behavior of fabrics was also studied. It was observed that for same fabric weight, protective performance and air permeability of satin woven fabrics were better as compared to the fabrics of other patterns. Protective performance increased and air permeability decreased as fabric weight increased for each type of woven structure included in this study. A new structural parameter is proposed which primarily influences the protective performance of fabrics exposed to either radiant heat, flame, or combined convective/radiant heat exposure.